Tax Reform Evaluation Using Nonparametric Methods: Sweden 1980 - 1991 - Sören Blomquist; Matias Eklöf; Whitney Newey (Uppsala University, Department of Economics, 1997)
This paper evaluates the tax reforms carried out in Sweden between 1980 and 1991. We use a recently developed nonparametric labor supply function to account for the behavorial responses of the taxed individuals. We decompose the tax reform to study how the separate components influence hours of work, tax revenues and income distribution. The results indicate that the reform was underfinanced and that the increased indirect taxation and redesigned transfer system almost eliminated the positive effects on hours of work due to the decreased marginal taxes on labor income. Further, we compare the results to the predictions of a parametric estimated labor supply model. The responses of the parametric model is almost twice the size of the nonparametric.
urn:nbn:se:uu:diva-2398
Keywords: C14; D31; H31; J22; 330; Nonparametric estimation; labor supply; tax revenues; income distribution